ANALYSIS IMPLEMENTATION OF TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE BY SCIENCE TEACHERS THROUGH DISTANCE LEARNING AT JUNIOR HIGH SCHOOL IN MEDAN - Sihombing, Rizky Agassy; Manurung, Grace Angeline; Simanjuntak, Lia Angraini (Jurnal Pendidikan Matematika dan IPA, 2022)
This research aims to analyze the application of the TPACK framework by teachers in distance learning at junior high schools in Medan. Curriculum 2013 in Indonesia been applying for 5 years. However, an evaluation of how does the teacher deliver learning subjects (pedagogy knowledge), and the implementation of subject mastery (content knowledge) and technology mastery (technology knowledge) is strongly suggested. In this research also used a qualitative descriptive method by providing a google form questionnaire to 10 junior high school teachers in the city of Medan as samples drawn with simple random sampling. The data was obtained based on the answers to questions from 10 junior high school science teachers, where 7 teachers were public school educators and the other 3 teachers were educators in private schools from different schools. The process of collecting data through a questionnaire containing questions that must be filled in by the teacher about their agreement or disagreement with the questions given in the questionnaire (Likert scale). The questions made are invincible with TPACK aspect. Based on the instruments that have been developed, researchers have obtained that the teachers already know and apply TPACK in distance learning well through the understanding and abilities possessed by the junior high school science teachers in carrying out the learning process in the classroom, especially on the topic of temperature and heat.